Pemanfaatan Media Sosial Instagram Sebagai Media Promosi Wisata Embung Sumberagung Kecamatan Gondang - Nadila Ayu Citra Armana; Nurul Azizah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The development of the reputation of today's tourist destinations cannot be separated from the role of technology. The use of social media that is connected to the internet as a tourism communication medium is now more flexible and profitable for all parties because the use of social media is considered easier to use and implement and has a very good effect. Its scope of influence is broad because it is not limited by space and time. In addition, the use of social media can be said to be cost-effective for disseminating various information about existing or even developing tourist sites. These things ultimately make social media more attractive to both potential and casual users. In general, the communicative nature of social media is the right strategy for service users to provide as detailed information as possible to their users. Social media is considered as the most profitable and effective marketing trend. The Internet has made marketing products more useful because it allows for more efficient, responsive and cost-effective marketing processes. In addition, fast response is also one of the advantages that is often used in social media promotions. The more routine these things are uploaded, the more familiar Instagram users are with the place so that over time the users are moved to visit tours. In this day and age, people tend to seek information through social media such as Instagram because it makes it easier for people to get information quickly and completely.